Labour market adjustment in Europe during the crisis: Microeconomic evidence from the Wage Dynamics Network survey - Mario Izquierdo; Juan Francisco Jimeno; Theodora Kosma; Ana Lamo; Stephen Millard; Tairi R\~o\~om; Eliana Viviano (European Central Bank (ECB), 2017)
Against the backdrop of continuing adjustment in EU labour markets in response to the Great Recession and the sovereign debt crisis, the European System of Central Banks (ESCB) conducted the third wave of the Wage Dynamics Network (WDN) survey in 2014-15 as a follow-up to the two previous WDN waves carried out in 2007 and 2009. The WDN survey collected information on wage-setting practices at the firm level. This third wave sampled about 25,000 firms in 25 European countries with the aim of assessing how firms adjusted wages and employment in response to the various shocks and labour market reforms that took place in the European Union (EU) during the period 2010-13. This paper summarises the main results of WDN3 by identifying some patterns in firms' adjustments and labour market reforms. It seeks to lay out the main lessons learnt from the survey in terms of both the general response of EU labour markets to the crisis and how these responses varied across the countries that took part in the survey.
Keywords: E24; J30; J52; J68; 330; Wage Dynamics Network; Survey data; Labour market adjustment; Labour market reforms; Arbeitsmarkt; Wirtschaftliche Anpassung; Schuldenkrise; Schock; Arbeitskosten; Lohnrigidität; Arbeitsmarktreform; EU-Staaten